Excitation energies of molecules by time-dependent density functional theory based on effective exact exchange Kohn-Sham potentials - Della Sala, Fabio; Görling, Andreas (International Journal of Quantum Chemistry, 2003)
An exchange-only approach to calculate both valence and Rydberg excitation energies within time-dependent density functional theory is presented. The ground-state Kohn-Sham (KS) orbitals and eigenvalues are evaluated using an effective exact-exchange KS potential, the localized Hartree-Fock potential. The exchange correlation kernel is taken into account within the adiabatic exchange-only local density approximation. Results for the nitrogen molecule, ethylene, and benzene are presented. The calculated excitation energies exhibit the same accuracy as those obtained using various empirically parameterized asymptotically corrected exchange correlation KS potential although no empirical parameters are used and correlation is completely neglected. © 2002 Wiley Periodicals, Inc. Int. J. Quantum. Chem. 91.